Teacher Professional Development Strategy Based on Human Performance Technology (HPT) to Improve the Quality of Authentic Evaluation - Krisna Murti Anugraha; Sabariah; Indah Zulaila Rahayu (Universitas Negeri Surabaya, 2026)
The need to improve assessment quality in 21st-century learning highlights the importance of authentic assessment in developing students’ critical thinking, creativity, and problem-solving skills. However, many elementary school teachers still face difficulties in designing authentic assessment effectively. This study aims to analyze the performance gap of teachers in designing authentic assessment and to formulate intervention strategies based on Human Performance Technology (HPT) to improve assessment design quality. The research employed a quantitative descriptive approach using a performance gap analysis design. The participants were 11 teachers from SDN Plemehan 2 Sumobito, Jombang Regency, selected purposively. Data were collected through a questionnaire based on five HPT components and analyzed using descriptive statistics with SPSS version 26. The results show that the overall average score falls into the good category, with the highest score in the motivation component (mean = 4.09; 81.8%) and the lowest in knowledge and skills (mean = 3.07; 61.4%). These findings indicate that teachers have strong motivation to implement authentic assessment but still require improvement in conceptual understanding and technical skills in assessment design. Based on the identified performance gaps, several intervention strategies are recommended, including practice-based micro training, strengthening data-driven feedback systems, developing Professional Learning Communities (PLC), and optimizing school technological resources. The study proposes an HPT-based teacher professional development framework that is contextual, measurable, and sustainable, which can serve as a strategic model to improve the quality of authentic assessment implementation in elementary schools.